Effects of OsNRT2.3b transgenosis on lettuce antioxidant capacity and nitrogen metabolism under low nitrogen - Yuxuan Qian; Xue Liu; Baoju Wang; Ning Liu; Dayong Li; Zhanhui Wu; Jing Tong (PLoS ONE, 2026)
Nitrate (NO 3 - ) plays dual roles in vascular plants, functioning as both an essential macronutrient and a phytoactive signaling compound. Research indicates that the high-affinity NO 3 - transporter OsNRT2.3b orchestrates fundamental agronomic traits, including biomass accumulation, grain production, and nitrogen (N) metabolism efficiency in cultivated rice. In this study, transgenic lettuce lines of OsNRT2.3b were generated, from which four lines with high OsNRT2.3b expression (OE20−5, OE21−7, OE21−11, and OE21−13) were selected and subjected to normal (CK) and low nitrogen (LN) treatments for 12 d. The results indicate that OsNRT2.3b transgenosis increased chlorophyll and glutathione (GSH) contents, as well as the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), in lettuce. However, OsNRT2.3b transgenosis had little effect on certain agronomic traits (leaf number, plant height, and leaf dimensions) of lettuce. Compared to the wild-type (WT), OsNRT2.3b transgenosis substantially enhanced the contents of NO 3 - , ammonium (NH 4 + ), amino acids, soluble protein, and the activities of NO 3 - reductase (NR), nitrite (NO 2 - ) reductase (NiR), glutamine synthetase (GS), and glutamate synthetase (GOGAT) in lettuce. Thus, OsNRT2.3b transgenosis improves the antioxidant capacity, photosynthetic level, and N use efficiency of lettuce. This research provides theoretical references for improving the N utilization efficiency of lettuce and enhancing its antioxidant capacity.